The Influence of Organizational Culture and Visionary Leadership on the Quality of Education Services at SMK Telkom Malang - Rahmat Dwi Djatmiko; Rina Djunita Pasaribu (Cita konsultindo, 2025)
The quality of educational services at SMK Telkom Malang contributes to student and parent satisfaction while fostering a conducive organizational culture. Visionary leadership plays a crucial role in establishing a clear vision, motivating school elements, and driving innovation through facility improvements and teacher development, creating a comfortable and productive learning environment. However, the declining trend in the Net Promoter Score (NPS) from 44.36 in 2022 to 35.21 in 2024, along with a decrease in new student enrollment over the past seven years, highlights the need for improvement. This study aims to analyze the influence of organizational culture and visionary leadership on the quality of educational services at SMK Telkom Malang within the context of vocational secondary education. This study employs a quantitative approach, with data collected through questionnaires distributed to respondents. Data analysis was conducted using descriptive analysis and multiple linear regression methods with the assistance of SPSS software. The study used 154 respondents as the research sample, drawn from the total population using proportionate stratified random sampling techniques. The population consists of school management, teachers, staff, and students from grades X to XII at SMK Telkom Malang. The findings of this study conclude: 1) there is a significant positive influence of organizational culture on the quality of educational services at SMK Telkom Malang; 2) there is a significant positive influence of visionary leadership on the quality of educational services at SMK Telkom Malang; 3) there is a significant simultaneous positive influence of organizational culture and visionary leadership on the quality of educational services at SMK Telkom Malang; and 4) the descriptive data reveals that respondents' scores for organizational culture tend to fall in the low category, while scores for visionary leadership and educational service quality are in the moderate category. Based on these findings, it is recommended that SMK Telkom Malang strengthens its organizational culture to create an educational environment that is adaptive and responsive to student needs. The school should maintain inspirational visionary leadership to support the achievement of its long-term vision. Additionally, the quality of educational services should be enhanced through the optimization of facilities, programs, safety, comfort, and the commitment of all members of the academic community.